The Influence of Brand Image and Product Quality on Customer Loyalty with Consumer Satisfaction as a Intervening Variable at Home Industry - Muhammad Arif; Afrianti Syahputri (Journal of International Conference Proceedings (JICP), 2021)
This study aims to determine the effect of brand image and product quality on customer loyalty through consumer satisfaction as an intervening variable in the H3soy soy milk MSME business. This research is an associative research and quantitative research with data collection techniques through a questionnaire/questionnaire. The population in this study were hesoy soy milk customers and the sample in this study amounted to 70 MSME customers of H3soy soy milk as the research sample. The results showed that brand image has a significant effect on consumer satisfaction, it is based on the p value of the two variables is 0.003. Brand image has no significant effect on customer loyalty, it is based on the p value of the two variables is 0.336. Product quality has a significant effect on consumer satisfaction, it is based on the p value of the two variables is 0.004. Product quality has no significant effect on customer loyalty, it is based on the p value of the two variables is 0.108. Consumer satisfaction has a significant effect on customer loyalty, it is based on the p value of the two variables is 0.015. Brand image has a significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.046. Product quality has no significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.089. Product quality has no significant effect on customer loyalty, it is based on the p value of the two variables is 0.108. Consumer satisfaction has a significant effect on customer loyalty, it is based on the p value of the two variables is 0.015. Brand image has a significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.046. Product quality has no significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.089. Product quality has no significant effect on customer loyalty, it is based on the p value of the two variables is 0.108. Consumer satisfaction has a significant effect on customer loyalty, it is based on the p value of the two variables is 0.015. Brand image has a significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.046. Product quality has no significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.089. Consumer satisfaction has a significant effect on customer loyalty, it is based on the p value of the two variables is 0.015. Brand image has a significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.046. Product quality has no significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.089. Consumer satisfaction has a significant effect on customer loyalty, it is based on the p value of the two variables is 0.015. Brand image has a significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.046. Product quality has no significant effect on customer loyalty through customer satisfaction as an intervening variable, it is based on the p value of the variable is 0.089.